Recovery of zinc as zinc phosphate and by-products from hydrometallurgical treatment of hot-dip galvanizing (Zn-Al) dross. (2021) - Sinha, Shivendra; Choudhari, R.; Shekhar, S.; Mishra, D.; Sahu, K.K.
Abstract: Zinc dross is the waste product generated during the hot-dip galvanizing, wherein around 11% of the total zinc is arrested by the dross leading to huge zinc losses. Though, there exist several pyro-metallurgical approaches to recover zinc but these are highly energy and cost intensive process; where hydrometallurgical processes take an edge. In this regard, this study holistically focusses on the hydrometallurgical recovery of zinc as zinc phosphate and other impurities like Al as alumina from zinc dross (Zn-Al) obtained from in-house hot-dip galvanizing unit at our laboratory. Zinc dross is leached as received in aqueous sulphuric acid medium without pulverization and stirring requirements, followed by separation of aluminium using NaOH based precipitation. Aluminium hydroxide precipitate is calcined to obtain alumina, whereas the supernatant solution is subsequently treated with disodium hydrogen phosphate to obtain products like zinc phosphate and sodium sulphate. The proposed process is simple, facile and scalable for recovery of zinc and other valuables from dross.